Barriers and facilitators to patient and public engagement and recruitment to digital health interventions: protocol of a systematic review of qualitative studies. Issue 9 (2nd September 2016) - O'Connor, Siobhan; Hanlon, Peter; O'Donnell, Catherine A; Garcia, Sonia; Glanville, Julie; Mair, Frances S
Abstract : Introduction: Patients and the public are beginning to use digital health tools to assist in managing chronic illness, support independent living and self-care, and remain connected to health and care providers. However, engaging with and enrolling in digital health interventions, such as telehealth systems, mobile health applications, patient portals and personal health records, in order to use them varies considerably. Many factors affect people's ability to engage with and sign up to digital health platforms. Objectives: The primary aim is to identify the barriers and facilitators patients and the public experience to engagement and recruitment to digital health interventions. The secondary aim is to identify engagement and enrolment strategies, leading if possible to a taxonomy of such approaches, and a conceptual framework of digital health engagement and recruitment processes. Methods: A systematic review of qualitative studies will be conducted by searching six databases: MEDLINE, CINAHL, PubMed, EMBASE, Scopus and the ACM Digital Library for papers published between 2000 and 2015. Titles and abstracts along with full-text papers will be screened by two independent reviewers against predetermined inclusion and exclusion criteria. A data extraction form will be used to provide details of the included studies. Quality assessment will be conducted using the Consolidated Criteria for Reporting Qualitative Research checklist. Any disagreements will be resolved through discussion with an independent third reviewer. Analysis will be guided by framework synthesis and informed by normalization process theory and burden of treatment theory, to aid conceptualisation of digital health engagement and recruitment processes. Discussion: This systematic review of qualitative studies will explore factors affecting engagement and enrolment in digital health interventions. It will advance our understanding of readiness for digital health by examining the complex factors that affect patients' and the public's ability to take part. Trial registration number: CRD42015029846.